“Keeping Moving”: factors associated with sedentary behaviour among older people recruited to an exercise promotion trial in general practice - Heseltine, Ruth; Skelton, Dawn.A.; Kendrick, Denise; Morris, Richard.W.; Griffin, Mark; Haworth, Deborah; Masud, Tahir; Iliffe, Steve (BioMed Central, 2015)
Background